Japanese women in education: a retrospective and future vision - Yoshiko Yamaguchi (FahrenHouse, 2011)
This article illustrates the evolution of Japanese female education based on feminist criti- cism of two events in Japan's history; the establishment of the modern education system which occurred during the Meiji Restoration at the end of the nineteenth century, and the post-war reform after the Second World War which was directed by the Allied Forces. The argument is supported not only by data from the Ministry of Education, but also with qualitative aspects of sexism which have been insidiously validated through the course of its development. In doing so, the article is aimed at recovering women's contribution within the educational system and reconfirming the significant role of gender studies.